Delivery of novel coumarin–dihydropyrimidinone conjugates through mixed polymeric nanoparticles to potentiate therapeutic efficacy against triple-negative breast cancer. (14th July 2021) - Ghosh, Avijit; Upadhyay, Priyanka; Sarker, Sushmita; Das, Shaswati; Bhattacharjee, Mousumi; Bhattacharya, Saurav; Ahir, Manisha; Guria, Subhajit; Gupta, Payal; Chattopadhyay, Sreya; Ghosh, Swatilekha; Adhikari, Susanta; et al.
Abstract : Coumarin–dihydropyrimidinone conjugates (CDHPs) and their poly(lactic- co -glycolic acid) (PLGA)-PEG4000 mixed copolymer nanoparticles as excellent chemotherapeutic nanomedicine to control TNBC. Abstract : To date, most of the accessible therapeutic options are virtually non-responsive towards triple-negative breast cancer (TNBC) due to its highly aggressive and metastatic nature. Interestingly, chemotherapy reacts soundly in many TNBC cases compared to other types of breast cancer. However, the side effects of many chemotherapeutic agents are still under cross-examination, and thus prohibit their extensive uses. In this present study, we have developed a series of coumarin–dihydropyrimidinone conjugates (CDHPs) and subsequently their poly(lactic- co -glycolic acid) (PLGA)-PEG4000 mixed copolymer nanoparticles as excellent chemotherapeutic nanomedicine to control TNBC. Among all the synthesized CDHPs, CDHP-4 (prepared by the combination of EDCO with 3, 4-difluorobenzaldehyde) showed excellent therapeutic effect on a wide variety of cancer cell lines, including TNBC. Besides, it can control the metastasis and stemness property of TNBC. Furthermore, the nano-encapsulation of CDHP-4 in a mixed polymer nanoparticle system (CDHP-4@PP-NPs) and simultaneous delivery showed much improved therapeutic efficacy at a much lower dose, and almost negligible side effects in normal healthy cells or organs. The effectiveness of the present therapeutic agent was observed both in intravenous and oral mode of administration in in vivo experiments. Moreover, on elucidating the molecular mechanism, we found that CDHP-4@PP-NPs could exhibit apoptotic, anti-migratory, as well as anti-stemness activity against TNBC cell lines through the downregulation of miR-138. We validated our findings in MDA-MB-231 xenograft chick embryos, as well as in 4T1-induced mammary tumor-bearing BALB/c mice models, and studied the bio-distribution of CDHP-4@PP-NPs on the basis of the photoluminescence property of nanoparticles. Our recent study, hence for the first time, unravels the synthesis of CDHP-4@PP-NPs and the molecular mechanism behind the anti-migration, anti-stemness and anti-tumor efficacy of the nanoparticles against the TNBC cells through the miR-138/p65/TUSC2 axis.